Religious and Cultural Use of Plant Resources by Baram Tribe - Devkota, Balak (Educational Journal, 2023)
Plants have been used by the humans since the ancient times. Indigenous people have sound knowledge of using floral species in their cultural rituals and customs. The use of such resources depends on indigenous knowledge gained from ancestral experience. So this study was carried out to explore the traditional use of plant species in their culture and religious customs of Barams in their ancestral place (Barpak-Sulikot Municipality of the Gorkha district) under ethnographic research design. Total of six elder people having the socio--cultural knowledge (are also the healers) were selected purposively for the study. In-depth interview and observation with ethic perspective was done frequently from 2076 to 2078 BS. Following the qualitative technique of data analysis, information was analyzed and interpreted thematically. The result shows that Barams have rich indigenous knowledge of using plant resources. They depend on floral resources for medicine, food, fodder, timber and firewood etc. aligning with the cultural and religious use. Total of 29 species were used in total of six worships or festivals and total of 13 species were used in four different cultural rituals of the Baram.